Position Control Algorithms of Photovoltaic Panels with Respect to the Incidence of Sunlight (LACCEI, 2024)
This paper shows the design and operation of a one-axis sun position tracker prototype for use in energy harvesting systems with photovoltaic panels. The prototype design is characterized by using low-cost control elements that allow applying the control algorithms in a simple way using Matlab/Simulink for the development and execution of the PID, FUZZY and PREDICTIVE control algorithms, to evaluate their operation independently in the sun position follower prototype. The control parameters to be considered for the evaluation are the percentage over level, the time and the error in steady state. An external light is used to simulate sunlight, making it possible to show that the predictive controller obtains the best results compared to the other two controllers used.